The Examination of Brand Switching Behaviour in Cosmetic Industry - Cheng, I-Jiun (2007)
Cometic industry is a lucrative business that progressively attracts more attentions from marketing research. The highly competitive environment in the cosmetic industry makes it a valuable area to study consumer behaviours. Brand switching behaviour is one of the most important consumer behaviours which is significant for the management to sustain competitive advantages in the global market. In this research, the relationship between brand switching behaviour and factors influencing such behaviour will be unveiled, with special focus on advertising, word-of-mouth advertising and promotions.